Nuclear magnetic resonances in (In,Ga)As/GaAs quantum dots studied by resonant optical pumping - Kuznetsova, M. S.; Flisinski, K.; Gerlovin, I. Ya.; Petrov, M. Yu.; Ignatiev, I. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

All-optical tomography of electron spins in (In,Ga)As quantum dots - Varwig, S.; René, A.; Economou, Sophia E.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Reinecke, T. L.; Bayer, M. (Physical Review B)

Polarization properties of single zinc-blende GaN/AlN quantum dots - Sergent, S.; Kako, S.; Bürger, M.; Schupp, T.; As, Donat Josef; Arakawa, Y. (Physical Review B)

Oxygen adsorbates on the Si(111)4×1-In metallic atomic wire: Scanning tunneling microscopy and density-functional theory calculations - Oh, Deok Mahn; Wippermann, S.; Schmidt, Wolf Gero; Yeom, Han Woong (Physical Review B)

Rashba splitting and relativistic energy shifts in In/Si(111) nanowires - Gerstmann, Uwe; Vollmers, N. J.; Lücke, A.; Babilon, M.; Schmidt, Wolf Gero (Physical Review B)

IntrinsicLiNbO3point defects from hybrid density functional calculations - Li, Yanlu; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

Unraveling theLiNbO3X-cut surface by atomic force microscopy and density functional theory - Sanna, S.; Schmidt, Wolf Gero; Rode, S.; Klassen, S.; Kühnle, A. (Physical Review B)

Information processing with topologically protected vortex memories in exciton-polariton condensates - Sigurdsson, H.; Egorov, O. A.; Ma, Xuekai; Shelykh, I. A.; Liew, T. C. H. (Physical Review B)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Influence of Coulomb-induced band couplings on linear excitonic absorption spectra of semiconducting carbon nanotubes - Liu, Hong; Schumacher, Stefan; Meier, Torsten (Physical Review B)
Starting from the extended Su-Schrieffer-Heeger model, multiband semiconductor Bloch equations are formulated in momentum space and applied to the analysis of the linear optical response of semiconducting carbon nanotubes (SCNTs). This formalism includes the coupling of electron-hole pair excitations between different valence and conduction bands, originating from the electron-hole Coulomb attraction. The influence of these couplings, which are referred to as nondiagonal interband Coulomb interaction (NDI-CI), on the linear excitonic absorption spectra is investigated and discussed for light fields polarized parallel to the tube direction. The results show that the intervalley NDI-CI leads to a significant increase of the band gap and a decrease of the exciton binding energy that results in a blueshift of the lowest-frequency excitonic absorption peak. The strength of these effects depends on the symmetry of the SCNT. Furthermore, for zigzag SCNTs with higher symmetry other nonintervalley NDI-CI terms also affect the spectral positions of excitonic absorption peaks.

Disordered graphene and boron nitride in a microwave tight-binding analog - Barkhofen, Sonja; Bellec, M.; Kuhl, U.; Mortessagne, F. (Physical Review B)

Combined influence of Coulomb interaction and polarons on the carrier dynamics in InGaAs quantum dots - Steinhoff, A.; Kurtze, H.; Gartner, P.; Florian, M.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Jahnke, F. (Physical Review B)

Picosecond real-space imaging of electron spin diffusion in GaAs - Henn, T.; Kiessling, T.; Ossau, W.; Molenkamp, L. W.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Hot carrier effects on the magneto-optical detection of electron spins in GaAs - Henn, T.; Heckel, A.; Beck, M.; Kiessling, T.; Ossau, W.; Molenkamp, L. W.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Hanle effect in (In,Ga)As quantum dots: Role of nuclear spin fluctuations - Kuznetsova, M. S.; Flisinski, K.; Gerlovin, I. Ya.; Ignatiev, I. V.; Kavokin, K. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Origins of conductance anomalies in ap-type GaAs quantum point contact - Komijani, Y.; Csontos, M.; Ihn, T.; Ensslin, K.; Meir, Y.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Influence of surface states on quantum and transport lifetimes in high-quality undoped heterostructures - Wang, D. Q.; Chen, J. C. H.; Klochan, O.; Das Gupta, K.; Reuter, Dirk; Wieck, A. D.; Ritchie, D. A.; Hamilton, A. R. (Physical Review B)

Scaling of the Kondo zero-bias peak in a hole quantum dot at finite temperatures - Klochan, O.; Micolich, A. P.; Hamilton, A. R.; Reuter, Dirk; Wieck, A. D.; Reininghaus, F.; Pletyukhov, M.; Schoeller, H. (Physical Review B)

Hot carrier effects on the magneto-optical detection of electron spins in GaAs - Henn, T.; Heckel, A.; Beck, M.; Kiessling, T.; Ossau, W.; Molenkamp, L. W.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Many-body correlations of electrostatically trapped dipolar excitons - Schinner, G. J.; Repp, J.; Schubert, E.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Govorov, A. O.; Holleitner, A. W.; Kotthaus, J. P. (Physical Review B)

Temperature dependence of hole spin coherence in (In,Ga)As quantum dots measured by mode-locking and echo techniques - Varwig, S.; René, A.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Fifth-order nonlinear optical response of excitonic states in an InAs quantum dot ensemble measured with two-dimensional spectroscopy - Moody, G.; Singh, R.; Li, H.; Akimov, I. A.; Bayer, M.; Reuter, Dirk; Wieck, A. D.; Cundiff, S. T. (Physical Review B)

Counting statistics of hole transfer in ap-type GaAs quantum dot with dense excitation spectrum - Komijani, Y.; Choi, T.; Nichele, F.; Ensslin, K.; Ihn, T.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Transverse optical instability patterns in semiconductor microcavities: Polariton scattering and low-intensity all-optical switching - Luk, M. H.; Tse, Y. C.; Kwong, N. H.; Leung, P. T.; Lewandowski, Przemyslaw; Binder, R.; Schumacher, Stefan (Physical Review B)

Charge compensation by long-period reconstruction in strongly polar lithium niobate surfaces - Sanna, S.; Rode, S.; Hölscher, R.; Klassen, S.; Marutschke, C.; Kobayashi, K.; Yamada, H.; Schmidt, Wolf Gero; Kühnle, A. (Physical Review B)

Femtosecond quantum interference control of electrical currents in GaAs: Signatures beyond the perturbative χ(3) limit - Sternemann, E.; Jostmeier, T.; Ruppert, C.; Duc, H. T.; Meier, Torsten; Betz, M. (Physical Review B)

Selection rules and linear absorption spectra of carbon nanotubes in axial magnetic fields - Liu, Hong; Schumacher, Stefan; Meier, Torsten (Physical Review B)
We derive a transparent and easy-to-use analytic expression for the selection rules and the optical dipole matrix elements for carbon nanotubes of arbitrary chirality in the presence of axial magnetic fields using a single-orbital π-electron tight-binding model. From this, we calculate the linear absorption spectrum for arbitrary polarization directions of the incident light, providing insight into all optically allowed transition. We show that the transverse absorption peaks can be selectively excited with circularly polarized light and spectrally resolved in an axial magnetic field.

Transition energies and direct-indirect band gap crossing in zinc-blende AlxGa1−xN - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero; Röppischer, Marcus; Cobet, Christoph; Esser, Norbert; Schupp, Thorsten; As, Donat J.; Feneberg, Martin; Goldhahn, Rüdiger (Physical Review B)

Origin of gate hysteresis inp-type Si-doped AlGaAs/GaAs heterostructures - Burke, A. M.; Waddington, D. E. J.; Carrad, D. J.; Lyttleton, R. W.; Tan, H. H.; Reece, P. J.; Klochan, O.; Hamilton, A. R.; Rai, A.; Reuter, Dirk; Wieck, A. D.; Micolich, A. P. (Physical Review B)

Hole spin precession in a (In,Ga)As quantum dot ensemble: From resonant spin amplification to spin mode locking - Varwig, S.; Schwan, A.; Barmscheid, D.; Müller, C.; Greilich, A.; Yugova, I. A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Transverse rectification in density-modulated two-dimensional electron gases - Ganczarczyk, A.; Rojek, S.; Quindeau, A.; Geller, M.; Hucht, A.; Notthoff, C.; König, J.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Noise thermometry in narrow two-dimensional electron gas heat baths connected to a quasi-one-dimensional interferometer - Buchholz, Sven S.; Sternemann, Elmar; Chiatti, Olivio; Reuter, Dirk; Wieck, Andreas D.; Fischer, Saskia F. (Physical Review B)

Hyperfine interaction mediated exciton spin relaxation in (In,Ga)As quantum dots - Kurtze, H.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Cyclotron-resonant exciton transfer between the nearly free and strongly localized radiative states of a two-dimensional hole gas in a high magnetic field - Bryja, L.; Jadczak, J.; Wójs, A.; Bartsch, G.; Yakovlev, D. R.; Bayer, M.; Plochocka, P.; Potemski, M.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Scaling coefficient for three-dimensional grain coalescence of ZnO on Si(111) - Ruth, Marcel; Meier, Cedrik (Physical Review B)

Enhanced photoluminescence of colloidal nanocrystals embedded in epitaxially grown semiconductor microstructures - Kampmeier, J.; Rashad, M.; Woggon, U.; Ruth, M.; Meier, Cedrik; Schikora, D.; Lischka, K.; Pawlis, A. (Physical Review B)

Optical properties of cubic GaN from 1 to 20 eV - Feneberg, Martin; Röppischer, Marcus; Cobet, Christoph; Esser, Norbert; Schörmann, Jörg; Schupp, Thorsten; As, Donat Josef; Hörich, Florian; Bläsing, Jürgen; Krost, Alois; Goldhahn, Rüdiger (Physical Review B)

Mapping the near-field dynamics in plasmon-induced transparency - Ye, Ziliang; Zhang, Shuang; Wang, Yuan; Park, Yong-Shik; Zentgraf, Thomas; Bartal, Guy; Yin, Xiaobo; Zhang, Xiang (Physical Review B)

Control of plasmon dynamics in coupled plasmonic hybrid mode microcavities - Lanzillotti-Kimura, N. D.; Zentgraf, Thomas; Zhang, X. (Physical Review B)

Slow-light dispersion by transparent waveguide plasmon polaritons - Ishikawa, Atsushi; Oulton, Rupert F.; Zentgraf, Thomas; Zhang, Xiang (Physical Review B)

Polarization-dependent methanol adsorption on lithium niobate Z-cut surfaces - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Physical Review B)

Atomic-resolution imaging of the polar (0001¯) surface of LiNbO3in aqueous solution by frequency modulation atomic force microscopy - Rode, S.; Hölscher, R.; Sanna, S.; Klassen, S.; Kobayashi, K.; Yamada, H.; Schmidt, Wolf Gero; Kühnle, A. (Physical Review B)

Fingerprints of order and disorder in the electronic and optical properties of crystalline and amorphous TiO2 - Landmann, M.; Köhler, T.; Köppen, S.; Rauls, E.; Frauenheim, T.; Schmidt, Wolf Gero (Physical Review B)

2-Aminopyrimidine-silver(I) based organic semiconductors: Electronic structure and optical response - Riefer, A.; Rauls, E.; Schmidt, Wolf Gero; Eberhard, J.; Stoll, I.; Mattay, J. (Physical Review B)

Many-body enhanced nonlinear conductance resonance in quantum channels - Han, Jong E.; Fischer, Saskia F.; Buchholz, Sven S.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D.; Bird, Jonathan P. (Physical Review B)

Generation and detection of mode-locked spin coherence in (In,Ga)As/GaAs quantum dots by laser pulses of long duration - Spatzek, S.; Varwig, S.; Glazov, M. M.; Yugova, I. A.; Schwan, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Edge-induced magnetoplasmon excitation in a two-dimensional electron gas under quantum Hall conditions - Notthoff, Christian; Reuter, Dirk; Wieck, Andreas D.; Lorke, Axel (Physical Review B)

Resonant nuclear spin pumping in (In,Ga)As quantum dots - Cherbunin, R. V.; Flisinski, K.; Gerlovin, I. Ya.; Ignatiev, I. V.; Kuznetsova, M. S.; Petrov, M. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Electrostatically trapping indirect excitons in coupled InxGa1−xAs quantum wells - Schinner, G. J.; Schubert, E.; Stallhofer, M. P.; Kotthaus, J. P.; Schuh, D.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Govorov, A. O. (Physical Review B)

Combinedab initioand classical potential simulation study on silicon carbide precipitation in silicon - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, Jörg; Schmidt, W. G.; Rauls, E. (Physical Review B)
Atomistic simulations on the silicon carbide precipitation in bulk silicon employing both, classical potential and first-principlesmethods are presented. The calculations aim at a comprehensive,microscopic understanding of the precipitation mechanism in the context of controversial discussions in the literature. For the quantum-mechanical treatment, basic processes assumed in the precipitation process are calculated in feasible systems of small size. The migration mechanism of a carbon 100 interstitial and silicon 11 0 self-interstitial in otherwise defect-free silicon are investigated using density functional theory calculations. The influence of a nearby vacancy, another carbon interstitial and a substitutional defect as well as a silicon self-interstitial has been investigated systematically. Interactions of various combinations of defects have been characterized including a couple of selected migration pathways within these configurations. Most of the investigated pairs of defects tend to agglomerate allowing for a reduction in strain. The formation of structures involving strong carbon–carbon bonds turns out to be very unlikely. In contrast, substitutional carbon occurs in all probability. A long range capture radius has been observed for pairs of interstitial carbon as well as interstitial carbon and vacancies. A rather small capture radius is predicted for substitutional carbon and silicon self-interstitials. Initial assumptions regarding the precipitation mechanism of silicon carbide in bulk silicon are established and conformability to experimental findings is discussed. Furthermore, results of the accurate first-principles calculations on defects and carbon diffusion in silicon are compared to results of classical potential simulations revealing significant limitations of the latter method. An approach to work around this problem is proposed. Finally, results of the classical potential molecular dynamics simulations of large systems are examined, which reinforce previous assumptions and give further insight into basic processes involved in the silicon carbide transition.

Tailoring the photonic band splitting in metallodielectric photonic crystal superlattices - Utikal, Tobias; Zentgraf, Thomas; Tikhodeev, Sergei G.; Lippitz, Markus; Giessen, Harald (Physical Review B)